Motor domain phosphorylation and regulation of the Drosophila kinesin 13, KLP10A. - Mennella, V.; Tan, D.Y.; Buster, D.W.; Asenjo, A.B.; Rath, U.; Ma, A.; Sosa, H.J.; Sharp, D.J. (Journal of Cell Biology, 2009)
Microtubule (MT)-destabilizing kinesin 13s perform fundamental roles throughout the cell cycle. In this study, we show that the Drosophila melanogaster kinesin 13, KLP10A, is phosphorylated in vivo at a conserved serine (S573) positioned within the alpha-helix 5 of the motor domain. In vitro, a phosphomimic KLP10A S573E mutant displays a reduced capacity to depolymerize MTs but normal affinity for the MT lattice. In cells, replacement of endogenous KLP10A with KLP10A S573E dampens MT plus end dynamics throughout the cell cycle, whereas a nonphosphorylatable S573A mutant apparently enhances activity during mitosis. Electron microscopy suggests that KLP10A S573 phosphorylation alters its association with the MT lattice, whereas molecular dynamics simulations reveal how KLP10A phosphorylation can alter the kinesin-MT interface without changing important structural features within the motor's core. Finally, we identify casein kinase 1alpha as a possible candidate for KLP10A phosphorylation. We propose a model in which phosphorylation of the KLP10A motor domain provides a regulatory switch controlling the time and place of MT depolymerization.